Creating New Rural Communitas: The Case of China Taiwan’s Rural Regeneration - Li Wenqi; Li Zhang (Journal of Regional and City Planning, 2021)
Traditional sociological theory explains that a rural community is an enclosed unit. China’s fast modernization and urbanization, however, display a rather different phenomenon, where rural communities are changing into open communities, which face the dual task of rebuilding internal relations and expanding external resources. Based on this background and practical cognition, the theoretical framework of the ‘new rural communitas’ is proposed, which expands the common enclosed relationships in traditional rural communities into new, open co-construction relationships with endogenous power as core, government power as support, and social power as coordination, emphasizing the full cooperation of these three types of power. On the basis of the theory, this article employs the practice of the rural regeneration policy in Taiwan as an empirical case, and analyzes how these three types of power affect and cooperate with each other. Furthermore, interviews have been conducted with local community members, government officers, and social participants in three communities in Taiwan to give examples of three different types of new rural communitas. Finally, several suggestions toward constructing new rural communitas are discussed.   Abstrak. Teori tradisional dalam sosiologi menjelaskan bahwa komunitas perdesaan adalah unit yang tertutup. Modernisasi dan urbanisasi cepat yang terjadi di China menampilkan fenomena yang sedikit berbeda, dimana komunitas perdesaan berubah menjadi komunitas yang terbuka yang menghadapi tugas ganda membangun kembali hubungan internal dan memperluas sumber daya eksternal. Berdasarkan latar belakang dan kognisi praktis ini, kerangka teoritis ‘komunitas perdesaan baru’ diusulkan, sehingga dapat memperluas hubungan tertutup bersama dalam komunitas perdesaan tradisional menjadi hubungan ko-kontruksi baru yang terbuka dengan kekuatan endogen sebagai inti, kekuatan pemerintah sebagai pendukung, dan kekuasaan social sebagai koordinasi serta menekankan kerjasama penuh dari ketiga jenis kekuasaan tersebut. Berdasarkan teori tersebut, artikel ini menggunakan praktik kebijakan regenerasi perdesaan di Taiwan sebagai kasus empiris, dan menganalisis bagaimana ketiga jenis kekuasaan ini saling mempengaruhi dan bekerja sama. Selanjutnya, wawancara telah dilakukan dengan anggota masyarakat setempat, pejabat pemerintah, dan peserta sosial di tiga komunitas di Taiwan untuk memberikan contoh tiga jenis komunitas perdesaan baru yang berbeda. Akhirnya, beberapa  saran untuk membangun komunitas perdesaan baru juga dibahas.   Kata kunci. Komunitas perdesaan, komunitas, regenerasi perdesaan, Cina, Taiwan.